2007
DOI: 10.15517/rbt.v56i3.5698
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variations of meiofaunal communities from the western sector of the Gulf of Batabanó, Cuba: III. Vertical distribution

Abstract: Abstract:The vertical distribution of meiofauna within subtidal sediments was studied in four stations pertaining to mangrove or muddy flats habitats. In 2003, replicated samples were taken in dry (February) and wet (July) seasons at the Bacunagua Inlet, southwestern coast of Cuba. The abundance and number of meiofaunal taxa exhibited a vertical gradient possibly due to changes in the concentrations of oxygen and hydrogen sulphide, rather than food availability along this gradient. Nematodes are capable of dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…This pattern was expected, since several studies have shown the dominance of Nematoda in estuaries or beaches characterized by fine sediments (Ansari and Parulekar, 1993; Gomes and Rosa Filho, 2009; Baia and Venekey, 2019), while Copepoda (in their adult or larval form) are more common organisms in environments characterized by coarse sediments, such as reflective beaches with high-energy hydrodynamics (McLachlan, 1977; Martins et al ., 2015). This pattern occurs due to the high concentration of oxygen in sediments with coarser grains, and this is an ideal condition for Copepoda as they are highly sensitive to interstitial depletion of oxygen (McLachlan and Brown, 2006; Armenteros et al ., 2008). Additionally, Du et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This pattern was expected, since several studies have shown the dominance of Nematoda in estuaries or beaches characterized by fine sediments (Ansari and Parulekar, 1993; Gomes and Rosa Filho, 2009; Baia and Venekey, 2019), while Copepoda (in their adult or larval form) are more common organisms in environments characterized by coarse sediments, such as reflective beaches with high-energy hydrodynamics (McLachlan, 1977; Martins et al ., 2015). This pattern occurs due to the high concentration of oxygen in sediments with coarser grains, and this is an ideal condition for Copepoda as they are highly sensitive to interstitial depletion of oxygen (McLachlan and Brown, 2006; Armenteros et al ., 2008). Additionally, Du et al .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the highest densities in muddy environments occurred in the upper layers. The same pattern was observed in several meiofauna studies conducted in tidal flats with muddy sediments, whether they were in marine, estuarine (Armenteros et al ., 2008) or freshwater environments (Reinicke, 2000). In freshwater tidal flats, environmental conditions are similar to those of marine muddy flats, at least in terms of grain size composition, temperature and oxygen availability (Reinicke, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of meiofauna in the mangrove have been conducted in India (e.g., Krishnamurthy, Sultan Ali, Jeyaseelan, 1984;Ansari, Sreepada, Matondka, Parulekar, 1993;Kondalarao, 1983;Sarma, Wilsanand, 1994;Thilagavathi, Das, Saravanakumar, Raja, 2011), Australia (Hodda, Nicholas, 1985;Alongi, 1987aAlongi, , b, c, 1988Alongi, , 1990Alongi, Christoffersen, 1992;Abdullah, Lee, 2017), South Africa, Kenya and associated area (Dye, 1983a, b;Ólafsson, 1995;Ólafsson, Carlström, Ndaro, 2000;Mutua, 2013), Malaysia (Sasekumar, 1994;Somerfield, 1998;Gee, Somerfield, 1997), America (Hopper, Fell, Cefalu, 1973;Fell, Cefalu, Masters, Tallman, 1975), Caribbean islands (Armenteros et al, 2006) etc.…”
Section: Introductionmentioning
confidence: 99%